Interactive Infotainment Map Design as a Tourism Guide for Kampung Eco Taman Sari - Muhammad Richard Putra Darmawan; Muhammad Redintan Justin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2025)
The development of digital technology has opened new opportunities in the advancement of tourism information media, particularly in the form of interactive maps. This study aims to design and develop an interactive infotainment map as a tourism guide for Kampung Eco Taman Sari, located in Pringsewu, Lampung. The design method was carried out through direct observation and interviews with the site management. The map adopts a nature-inspired theme with a 2D visual style and a horizontal layout that displays various numbered interactive icons such as fishing areas, paddle boat rides, swimming pools, photo spots, and other facilities. The design process began with manual sketching, followed by digitalization using design software, and the creation of an interactive prototype using Figma based on user interface (UI) and user experience (UX) design approaches. The resulting design features interactive elements such as icons, nature-themed color palettes, and a click-based navigation system that is easy for users to understand. This map is designed to be accessible through digital devices with a user-friendly interface, supporting efficient and enjoyable exploration. The final result is an informative digital map, the interactive infotainment map, which is expected to enhance the overall visitor experience while strengthening Eco Taman Sari’s image as a leading ecotourism destination in Lampung.